2022
DOI: 10.21608/ejhm.2022.215203
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students' Satisfaction Regarding Blended Learning during COVID-19 Pandemic

Abstract: Background: The realization of the profession's role in both of global and personal concept affected the self-identification among 2020 medical students. COVID-19 pandemic can hinder, accelerate, or change medical students' professional identity formation. Objective: To assess the level of satisfaction about blended learning among undergraduate medical students at Zagazig University and to determine challenges, which face the medical students during blended learning education in Faculty of Medicine. Patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The current study found a statistically significant link between student satisfaction and their age, consistent with previous findings unveiling a significant association between age and student level of satisfaction, where older students tended to be more satisfied than younger ones (El-Hawy et al, 2022), but contrary to others showing that age did not significantly affect student satisfaction (Venkatesh et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…The current study found a statistically significant link between student satisfaction and their age, consistent with previous findings unveiling a significant association between age and student level of satisfaction, where older students tended to be more satisfied than younger ones (El-Hawy et al, 2022), but contrary to others showing that age did not significantly affect student satisfaction (Venkatesh et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…The key factor in determining the quality of blended learning is students' satisfaction through measuring students' level of pleasure and the efficacy of the student's education experience (Dinh et al, 2021). The main objective of any educational program is to be satisfied with this program, which leads to the success and continuation of the learning package because it confirms the effectiveness of the educational process and increases its efficiency (El-Hawy et al, 2022).…”
Section: Discussionmentioning
confidence: 99%